(untitled) (International Journal of Innovative Technologies in Economy, 2018)
Decisions of Oracle Cloud are developed for the purpose of safety for infrastructures and platforms. Data protection is one of the main questions by development of all types of infrastructures and services of Oracle for a public cloud. Decisions of Oracle Cloud were developed with the purpose to ensure safety for infrastructures and platforms, executing crucial operational loads and data storage. Oracle easily provides the high level of protection, to cope with confidence with any operational loads and creates reliable hybrid cloudy decisions providing simple control and monitoring from local systems and convenient transfer of operational loads.